2016
DOI: 10.26740/jpfa.v6n2.p61-69
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Hasil Analisis Miskonsepsi Gerak Menggunakan Instrumen Diagnostik Three Tier Pada Siswa SMP

Abstract: Miskonsepsi adalah konsepsi siswa yang tidak sesuai dengan konsepsi para ilmuwan. Miskonsepsi terjadi secara konsisten di dalam pikiran siswa dalam menafsirkan konsep menjadi konsepsi dan atau dalam penerapannya menjadi fakta. Mata pelajaran IPA sering menimbulkan kesulitan siswa dalam memahami konsep-konsep yang abstrak. Hasil analisis miskonsepsi menggunakan instrumen diagnostik three tier, selanjutnya dapat dilakukan identifikasi miskonsepsi untuk mengetahui jenis miskonsepsi yang terjadi. Penelitian ini me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
7
0
5
Order By: Relevance
“…Therefore, student's misconception should be detected earlier to prevent misconceptions in subsequent concepts. To do that, a conception diagnostic test is required, either using interviews, concept maps or multi-tiers conception diagnostic test (Wiyono et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, student's misconception should be detected earlier to prevent misconceptions in subsequent concepts. To do that, a conception diagnostic test is required, either using interviews, concept maps or multi-tiers conception diagnostic test (Wiyono et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Misconception category 3 (M3) was identified as the highest misconception of this indicator with a presentation of 42.22% or as many as 38 students. In line with Wiyono et al (2016) research, students have misconceptions, students assume that objects will maintain their initial position that moves by giving new movements in the opposite direction. The identified misconception of category 2 (M2) was 17.78%, or Alatas, F., Ilhamiah, S., Suryadi, A.…”
mentioning
confidence: 87%
“…Analysis data from student response questionnaire and observations of student activities using the Guttman scale by answering "Yes" and "No". Score 1 if "Yes" and score 0 if "No" (Wiyono et al, 2016). Guttman scale in this research is shown in Table 3.…”
Section: Mass Product Manufacturementioning
confidence: 99%